If f(x) -> oo and g(x) -> c, then f(x)g(x) -> -oo if c < 0

  • #1
911
18

Homework Statement


If ##\lim_{x \rightarrow a} f(x) =\infty## and ## \lim_{x \rightarrow a} g(x) = c##, then prove that $$\lim_{x \rightarrow a} \left[ f(x)g(x)\right] = -\infty ~\text{ if c < 0 }$$

Homework Equations


Epsilon Delta definition

The Attempt at a Solution


Let ##N<0## be arbitrary. Since ##c<0##, we have ##\frac{2N} c >0##. Since ##\lim_{x \rightarrow a} f(x) =\infty##, ##\exists~ \delta_1>0## such that $$\forall ~ x\in D(f)\left[ 0<|x-a| <\delta_1 \rightarrow f(x) > \frac{2N} c \right]\cdots\cdots(1)$$ Also ##-\frac c 2 >0##, and since ## \lim_{x \rightarrow a} g(x) = c##, ##\exists ~ \delta_2 >0 ## such that $$\forall ~x \in D(g) \left[ 0<|x-a| <\delta_2 \rightarrow |g(x) - c| < -\frac c 2 \right]\cdots\cdots(2)$$ Here ##D(f)## and ##D(g)## are the domains of functions ##f## and ##g##. Let ##\delta = \text{min}(\delta_1, \delta_2)## and let ##x_1 \in D(fg)## be arbitrary, where ##D(fg)## is the domain of function ##fg##. So we have ##x_1 \in D(f)## and ##x_1 \in D(g)##. Also suppose ##0<|x_1-a| <\delta ##. It follows that ##0<|x_1-a| <\delta_1## and ## 0<|x_1-a| <\delta_2##. So now using equations ##(1)## and ##(2)##, we deduce that ##f(x_1) > \frac{2N} c ## and ##|g(x_1)-c| < -\frac c2## It follows that ##g(x_1) < \frac c 2##. Since ##f(x_1) > \frac{2N} c > 0##, we get ## f(x_1)g(x_1) <f(x_1) \frac c 2##. But as ##f(x_1) > \frac{2N} c## , we have ##f(x_1)\frac c 2 < N##. It follows that ##f(x_1)g(x_1) < N##. As ##N<0## is arbitrary, and ##x_1 \in D(fg)## is arbitrary, from the definition it follows that $$\lim_{x \rightarrow a} \left[ f(x)g(x)\right] = -\infty ~\text{ if c < 0 }$$ Please check my proof. Thanx
 

Answers and Replies

  • #2
PeroK
Science Advisor
Homework Helper
Insights Author
Gold Member
13,774
6,263
Given your previous post, I would say there is no need to prove this explicitly, as it is just the same steps repeated. This results follows from the previous result. I think that is a better mathematical approach to deduce a similar result from a previous one than to go back to first principles and effectively repeat the same steps.
 
  • #3
911
18
Perok, I could have done that. But just wanted to hone my ##\epsilon-\delta## skills in these kinds of proofs.
 
  • #4
PeroK
Science Advisor
Homework Helper
Insights Author
Gold Member
13,774
6,263
Perok, I could have done that. But just wanted to hone my ##\epsilon-\delta## skills in these kinds of proofs.
Okay, but perhaps it's time to move on to more challenging problems.
 
  • #5
911
18
Slowly I am moving there
 
  • #6
Ray Vickson
Science Advisor
Homework Helper
Dearly Missed
10,706
1,728
Perok, I could have done that. But just wanted to hone my ##\epsilon-\delta## skills in these kinds of proofs.
But you are doing that at the expense of insight. You have proven the result already if ##g(x) \to c > 0##, so to know the result for ##g(x) \to c < 0## just apply the previous result to ##h(x) = -g(x)##, in which ##h(x) \to -c > 0##. That IS a proof!

When I mention "insight" I mean that someone wanting to become adept at Mathematics should try very hard to recognize similar cases already solved, and just apply previous results whenever possible. Repeating over and over the same type of argument does not enhance one's understanding, and might even be regarded as working against true understanding.
 
Last edited:
  • Like
Likes fresh_42 and PeroK
  • #7
911
18
Thanks Ray
 

Related Threads on If f(x) -> oo and g(x) -> c, then f(x)g(x) -> -oo if c < 0

Replies
8
Views
1K
Replies
6
Views
556
Replies
3
Views
7K
Replies
9
Views
2K
  • Last Post
Replies
3
Views
5K
  • Last Post
Replies
2
Views
1K
Replies
9
Views
607
Replies
3
Views
2K
Top